Influence of configuration chambers on the formation of stress in multi-modulus mass - Petlovanyi, M (National Mining University, 2016)
Purpose. Detecting unstable areas in the filling mass taking into account configuration of the adjacent mineable chambers to improve its formation. Methods. The research into stress state of multi-modulus mass consisting of ore, rocks and filling was conducted using SolidWorks 2011 software with the full compliance of their physical and mechanical properties. Findings. Computer simulation allowed to reveal unstable areas in the filling mass of the first stage chamber under the influence of the development of the second stage chamber. It was found that the vertical stress component forms an area of compressive stresses in the filling mass of the first stage chamber at the junction of its exposure to the roof of filling chamber with dimensions: depth of the mass – up to 50 m, vertical outcrop – 9.8 m, the maximum value of stress reaching 89 MPa. The horizontal stress component also forms an area of tensile stress, but with a lower value of 65 MPa. The horizontal stress component generates in the filling mass of the first stage chambers the area of tensile stresses on the substage level 775 – 810 m with dimensions: depth of the mass – up to 7 m, vertical exposure – 10 m, and the maximum stress value – up to 4 MPa. Originality. Analytical assessment of the filling mass stability allowed to conclude that: at the junction of its exposure to the roof of filling chamber, the compressive stress exceeds the strength of filling mass 1.8 times, in the center of filling mass on the outcrop, the tensile stress exceeds the strength of filling 1.3 times. Vertical stresses exceed horizontal stresses 1.35 times in the areas of filling destruction. Practical implications. The obtained findings related to the stress state of the filling mass can be used in issuing passports for stopes in choosing the filling mode and composition of the filling mixture.

Цель. Установление неустойчивых областей закладочного массива при влиянии отработки запасов руд в смежной камере посредством компьютерного моделирования для разработки путей повышения его устойчивости. Методика. Исследования напряженного состояния разномодульного массива, состоящего из руды, пород и закладки выполнены при помощи программного обеспечения SolidWorks 2011 с полным соответствием их физико-механических свойств. Результаты. Посредством компьютерного моделирования выявлены неустойчивые области в закладочном массиве камеры первой очереди под влиянием отработки камеры второй очереди. Установлено, что вертикальная компонента напряжений формирует область сжимающих напряжений в массиве закладки камеры первой очереди отработки на сопряжении ее обнажения с кровлей отрабатываемой камеры со следующими размерами: вглубь массива – до 50 м, по вертикали обнажения – 9.8 м, а максимальная величина напряжений достигает 89 МПа. В этой же области горизонтальная компонента формирует также область сжимающих напряжений, но с меньшим значением в 65 МПа. Горизонтальная компонента напряжений формирует в закладочном массиве камер первой очереди область растягивающих напряжений на уровне подэтажа 775 – 810 м при размерах: вглубь массива – до 7 м, по вертикали обнажения – 10 м, а максимальная величина напряжения достигает 4 МПа. Научная новизна. Дана аналитическая оценка устойчивости закладочного массива: на сопряжении его обнажения с кровлей отрабатываемой камеры – превышение сжимающих напряжений над прочностью закладки в 1.8 раз, в центре закладочного массива на обнажении – превышение растягивающих напряжений над прочностью закладки в 1.3 раза. Установлено, что вертикальные напряжения превосходят горизонтальные напряжения в областях разрушения закладки в 1.35 раз. Практическая значимость. Полученные результаты исследования напряженного состояния закладочного массива могут использоваться при проектировании паспортов на закладку выемочных камер при выборе режима заполнения и состава закладочной смеси.

Мета. Встановлення нестійких областей закладного масиву при впливі відпрацювання запасів руд у суміжній камері за допомогою комп’ютерного моделювання для розробки шляхів підвищення його стійкості. Методика. Дослідження напруженого стану різномодульного масиву, що складається з руди, порід та закладки виконані за допомогою програмного забезпечення SolidWorks 2011 з повною відповідністю їх фізико-механічних властивостей. Результати. За допомогою комп’ютерного моделювання виявлено нестійкі області у закладному масиві камери першої черги під впливом відпрацювання камери другої черги. Встановлено, що вертикальна компонента напружень формує область стискаючих напружень у масиві закладки камери першої черги відпрацювання на сполученні її відслонення з покрівлею камери, що відпрацьовується, з наступними розмірами: вглиб масиву – до 50 м, по вертикалі відслонення – 9.8 м, а максимальна величина напружень сягає 89 МПа. У цій же області горизонтальна компонента формує також область стискаючих напружень, , але з меншим значенням у 65 МПа. Горизонтальна компонента напружень формує у закладному масиві камер першої черги область розтягуючих напружень, на рівні підповерху 775 – 810 м при розмірах: вглиб масиву – до 7 м, по вертикалі відслонення – 10 м, а максимальна величина напруження сягає 4 МПа. Наукова новизна. Дана аналітична оцінка стійкості закладного масиву: на сполученні його відслонення з покрівлею камери, що відпрацьовується, – перевищення стискаючих напружень над міцністю закладки у 1.8 разів, в центрі закладного масиву на відслоненні – перевищення розтягуючих напружень над міцністю закладки у 1.3 рази. Встановлено, що вертикальні напруження перевищують горизонтальні в областях руйнування закладки у 1.35 разів. Практична значимість. Отримані результати дослідження напруженого стану закладного масиву можуть використовуватися при проектуванні паспортів на закладку виїмкових камер при виборі режиму заповнення та складу закладної суміші.
Вплив конфігурації очисних камер на формування напружень в різномодульному масиві
Влияние конфигурации очистных камер на формирование напряжений в разномодульном массиве
Keywords: Research Subject Categories::NATURAL SCIENCES::Earth sciences; stress state; strength; filling mass; chamber; chamber configuration